2005
DOI: 10.1200/jco.2005.13.466
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Single-Agent Temsirolimus (CCI-779) for Relapsed Mantle Cell Lymphoma

Abstract: Single-agent temsirolimus has substantial antitumor activity in relapsed MCL. This study demonstrates that agents that selectively target cellular pathways dysregulated in MCL cells can produce therapeutic benefit. Further studies of this agent in MCL and other lymphoid malignancies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
319
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(338 citation statements)
references
References 42 publications
13
319
2
4
Order By: Relevance
“…In a phase II clinical trial, the rapamycin derivative temsirolimus revealed significant clinical activity in patients with relapsed mantle cell lymphoma. 40 This drug was shown to hyper-induce autophagy and to elicit synergistic anti-tumour effect with vorinostat at low doses in mantle cell lymphoma cells; 41 (2) chloroquine is a well-known lysosomotropic anti-malarial drug that impairs intralysosomal proteolysis by alkalinizing the vacuolar pH. In myc-overexpressing transgenic mice that model human Burkitt's lymphoma, chloroquine administration prevented the development of myc-induced lymphomas by killing precancerous B lymphocytes through a p53-dependent and caspase-independent death pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II clinical trial, the rapamycin derivative temsirolimus revealed significant clinical activity in patients with relapsed mantle cell lymphoma. 40 This drug was shown to hyper-induce autophagy and to elicit synergistic anti-tumour effect with vorinostat at low doses in mantle cell lymphoma cells; 41 (2) chloroquine is a well-known lysosomotropic anti-malarial drug that impairs intralysosomal proteolysis by alkalinizing the vacuolar pH. In myc-overexpressing transgenic mice that model human Burkitt's lymphoma, chloroquine administration prevented the development of myc-induced lymphomas by killing precancerous B lymphocytes through a p53-dependent and caspase-independent death pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Results have been reported from studies in metastatic breast (MBC), renal cell (RCC), 75 small cell lung, (SCLC), 76 endometrial carcinoma, 77 mantle cell lymphoma (MCL), 78 melanoma, 79 and glioblastoma multiforme (GBM). 80,81 The results of these studies are summarized in Table 2.…”
Section: Temsirolimus (Cci-779)mentioning
confidence: 99%
“…Concentrations leading to apoptosis and autophagy are observed only at high concentrations barely compatible with pharmacokinetic exposures that may be reached in the patients. To our knowledge, tumour types highly vulnerable to rapalogues include endometrial cancer (Kanamori et al, 2001;Uegaki et al, 2005;Oza et al, 2006;Colombo et al, 2007;Milam et al, 2007) that frequently displays PTEN loss of function and mantle cell lymphoma (Grewe et al, 1999;Witzig et al, 2005;Ansell et al, 2006) that overexpress cyclin D1. The effects of rapalogues in mantle cell carcinoma are consistent with preclinical studies showing that mTORC1 inhibitors could downregulate cyclin D1 (Aguirre et al, 2004).…”
Section: Differential Review Of Biological Effects Of Mtor Inhibitionmentioning
confidence: 99%